POTENSI TENUN TRADISIONAL DAN PERIKANAN SEBAGAI PILAR EKONOMI DESA TERNATE SELATAN - Riflyisriany Beriledang; Trivonia Ata; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This research aims to analyze the potential of the fisheries and traditional weaving sectors as the main pillars of the economy of South Ternate Village, Alor Regency, East Nusa Tenggara Province. The study employs a qualitative approach, with data collected through field observations and in-depth interviews with community members and village officials. The findings indicate that the fisheries sector plays an important role in supporting the livelihoods of coastal communities through fishing activities that utilize local marine resources. Meanwhile, traditional weaving has developed as a culture-based economic activity that not only contributes to household income but also serves as a means of preserving customary values and the community’s social identity. Despite their significant potential, both the fisheries and traditional weaving sectors face constraints related to limited infrastructure, technology, capital, and market access. However, strong social cohesion, mutual cooperation, and local traditions constitute important social capital for the community. Therefore, this study recommends improving community skills, enhancing infrastructure, and strengthening village policy support to ensure the sustainable development of both sectors